2017
DOI: 10.1093/ije/dyx013
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to the Chinese famine of 1959–61 in early life and long-term health conditions: a systematic review and meta-analysis

Abstract: Our findings suggest that uncontrolled age differences between famine and post-famine births could explain most effects commonly attributed to the famine. For more reliable estimates of long-term famine effects in China, other analyses will be needed with age-appropriate controls and better information on the severity and timing of the famine in the populations included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
173
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(182 citation statements)
references
References 52 publications
7
173
2
Order By: Relevance
“…The differences between our findings and those from famine studies 814 highlight the potential heterogeneity in the physiological response to severe acute versus moderate non-wasting undernutrition. The mothers in the original trial were short but not underweight.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The differences between our findings and those from famine studies 814 highlight the potential heterogeneity in the physiological response to severe acute versus moderate non-wasting undernutrition. The mothers in the original trial were short but not underweight.…”
Section: Discussioncontrasting
confidence: 97%
“…13 However, not all famine episodes have been found to produce adverse health effects in later life. A review 14 concluded that health effects commonly attributed to the Great Chinese Famine can be explained by uncontrolled effects of age. The Leningrad Siege Study10 found no association between exposure to early-life starvation and later-life hypertension, dyslipidaemia, or glucose tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…This result is broadly in line with the work of Li and Lumey () which finds that Famine exposure increased the risk of schizophrenia but had no other long‐term negative impact on mental health.…”
Section: Resultssupporting
confidence: 90%
“…The subjects in the present study were born in the early 1960s, which maybe another reason for the apparent discrepancy between studies. In the early 1960s, China had just experienced severe famine, and some studies have found that experiencing famine or malnutrition in early life may increase susceptibility to diabetes …”
Section: Discussionmentioning
confidence: 99%